Enhanced Activity by NKCC1 and Slc26a6 Mediates Acidic pH and Cl− Movement after Cardioplegia-Induced Arrest of db/db Diabetic Heart. (8th September 2019) - Ji, Minjeong; In Lee, Seok; Lee, Sang Ah; Son, Kuk Hui; Hong, Jeong Hee
Abstract : Diabetic heart dysfunctions during cardiac surgeries have revealed several clinical problems associated with ion imbalance. However, the mechanism of ion imbalance mediated by cardioplegia and a diabetic heart is largely unclear. We hypothesized that ion transporters might be regulated differently in the diabetic heart and that the differentially regulated ion transporters may involve in ion imbalance of the diabetic heart after cardioplegic arrest. In this study, we modified the Langendorff-free cardioplegia method and identified the involved ion transporters after cardioplegia-induced arrest between wild type and db/db heart. Enhanced expression of Na + -K + -2Cl − cotransporter 1 (NKCC1) was observed in the db/db heart compared to the wild type heart. Enhanced NKCC1 activity was observed in the left ventricle of db/db mice compared to that of wild type after cardioplegia-induced arrest. The expression and activity of Slc26a6, a dominant Cl − /HCO3 − exchanger in cardiac tissues, were enhanced in left ventricle strips of db/db mice compared to that of wild type. The Cl − transporting activity in left ventricle strips of db/db mice was dramatically increased as compared to that of wild type. Interestingly, expression of Slc26a6, as well as carbonic anhydrase IV as a supportive enzyme of Slc26a6, was increased in db/db cardiac strips compared to wild type cardiac strips. Thus, the enhanced Cl − transporting activity and expression by NKCC1 and Slc26a6 in db/db cardiac tissues after cardioplegia-induced arrest provide greater insight into enhanced acidosis and Cl − movement-mediated db/db heart dysfunction. Thus, we suggested that enhanced Cl − influx and HCO3 − efflux through NKCC1 and Slc26a6 offer more acidic circumstances in the diabetic heart after cardioplegic arrest. These transporters should be considered as potential therapeutic targets to develop the next generation of cardioplegia solution for protection against ischemia-reperfusion injury in diabetic hearts.